Mutations which Introduce Free Cysteine Residues in the Gla-Domain of Vitamin K Dependent Proteins Result in the Formation of Complexes with α1-Microglobulin - Wojcik, E G C; Simioni, P; Berg, M v d; Girolami, A; Bertina, R M (Thrombosis and Haemostasis, 1996)
We have previously described a genetic factor IX variant (Cys18→Arg) for which we demonstrated that it had formed a heterodimer with armicroglobulin through formation of a disulphide bond with the remaining free cysteine residue of the disrupted disulphide bond in the Gla-domain of factor IX. Recently, we observed a similar high molecular weight complex for a genetic protein C variant (Arg-1→Cys). Both the factor IX and the protein C variants have a defect in the calcium induced conformation. In this study we show that the aminoterminus of this protein C variant is prolonged with one amino acid, cysteine. This protein C variant, as well as protein C variants with Arg9→Cys and Ser12→Cys mutations which also carry a free cysteine residue, are shown to be present in plasma as a complex with α1-microglobulin. A prothrombin variant with a Tyr44→Cys mutation, had not formed such a complex. Furthermore, complexes between normal vitamin K-dependent clotting factors and α1-microglobulin were shown to be present in plasma at low concentrations. The data suggest that the presence of an unpaired cysteine residue in the propeptide or the N-terminal half of the Gla-domain has strongly promoted the formation of a complex with α1-microglobulin in the variants.